Audit committee disclosure tone and earnings management. Issue 5 (24th May 2021) - Al-Shaer, Habiba; Zaman, Mahbub
Abstract : Purpose: This paper examines the effect of audit committee (AC) reporting, measured by the tone of audit committee disclosures, in improving financial reporting quality as proxied by earnings management. Design/methodology/approach: The authors focus on the textual properties of AC reports, particularly the tone of AC disclosure, and their impact on financial reporting quality proxied using real and accruals-based earnings management. For additional analysis, the authors use a financial reporting index and matched sample. The analysis is based on a sample of UK FTSE 350 firms. Findings: The analysis suggests that AC reports are not boilerplate but varied in language. The authors find AC reporting is negatively associated with both real and accruals-based earnings management. In our additional tests, the authors find a positive association between financial reporting quality index and reporting tone. Research limitations/implications: Overall, this paper provides baseline evidence for future research and policy making and reveals that ACs reporting what they have done increases transparency and impacts on reporting quality. Practical implications: Overall, this paper suggests that the tone of AC reports seems to convey information that affects the communication function of AC reporting and thereby helps to improve reporting quality. Originality/value: Though the importance of AC disclosures in improving reporting quality is well recognised in policy guidelines and governance recommendations, no study has employed computer-based textual analysis of AC reports and investigated the effect of AC disclosure tone and the role it can play in achieving higher reporting quality.